Cetyltrimethylammonium bromide in the synthesis of mesoporous silica nanoparticles: General aspects and in vitro toxicity - Carvalho, Gabriela Corrêa [UNESP]; Marena, Gabriel Davi [UNESP]; Karnopp, Juliana Camila Fischer; Jorge, Juliana; Sábio, Rafael Miguel [UNESP]; Martines, Marco Antonio Utrera; Bauab, Taís Maria [UNESP]; Chorilli, Marlus [UNESP] (Elsevier, 2022)
Pharmaceutical nanotechnology has become a trend with incalculable advantages in the applicability of systems in the controlled, safe and effective release of drugs. Among the nanotechnological nanoparticles, the mesoporous silica nanoparticles stand out, a system with significant biocompatibility, good physical chemical stability, greater surface contact area with desirable and adjustable pore structure. Once developed and well defined, these pores can carry drugs and control their release. However, to create this type of nanoparticle is essencial to use surfactants since they act as pore template. Among the most important surfactants, cetyltrimethylammonium bromide (CTAB) highlights, a quaternary ammonium compound widely used as a surfactant in the synthesis of mesoporous silica nanoparticles (MSNs), hollow mesoporous silica (HMSNs) and core-shell MSNs. However, for achieving good results of drug-loaded pores it is necessary to remove CTAB by extraction techniques, which provides pores formation throughout the silica and the incorporation of molecules. During and after the removal process, it is possible that CTAB residues remains inside the pores, despide several removal processes are described as efficient in the complete removal of surfactants. In turn, the presence of CTAB residues can be advantageous, especially when considering its antimicrobial activity. Meanwhile, it should be noted that the presence of CTAB may present high toxicity risks. This review seeks to explore not only general aspects of the use of CTAB in the synthesis of MSNs, but also to assess its toxicity in prokaryotic and eukaryotic cells, in order to determine whether CTAB residues are acceptable in MSNs that will be used as drug delivery systems for further in vivo and clinical assays.
Keywords: bacteria; Cetyltrimethylammonium bromide; fungi; Mammal cells; Mesoporous silica nanoparticles